Development of Antibody-Fragment–Producing Rice for Neutralization of Human Norovirus - Sasou, Ai; Yuki, Yoshikazu; Kurokawa, Shiho; Sato, Shintaro; Goda, Yuki; Uchida, Masao; Matsumoto, Naomi; Sagara, Hiroshi; Watanabe, Yuji; Kuroda, Masaharu; Sakon, Naomi; Sugiura, Kotomi; et al. (Frontiers in Plant Science, 2021)
Human norovirus is the leading cause of acute nonbacterial gastroenteritis in people of all ages worldwide. Currently, no licensed norovirus vaccine, pharmaceutical drug, or therapy is available for the control of norovirus infection. Here, we used a rice transgenic system, MucoRice, to produce a variable domain of a llama heavy-chain antibody fragment (VHH) specific for human norovirus (MucoRice-VHH). VHH is a small heat- and acid-stable protein that resembles a monoclonal antibody. Consequently, VHHs have become attractive and useful antibodies for oral immunotherapy against intestinal infectious diseases. MucoRice-VHH constructs were generated at high yields in rice seeds by using an overexpression system with RNAi to suppress the production of the major rice endogenous storage proteins. The average production levels of monomeric VHH (7C6) to GII.4 norovirus and heterodimeric VHH (7C6-1E4) to GII.4 and GII.17 noroviruses in rice seed were 0.54% and 0.28% (w/w), respectively, as phosphate buffered saline (PBS)-soluble VHHs. By using a human norovirus propagation system in human induced pluripotent stem-cell-derived intestinal epithelial cells, we demonstrated the high neutralizing activity of MucoRice expressing monomeric VHH (7C6) against GII.4 norovirus and of heterodimeric VHH (7C6-1E4) against both GII.4 and GII.17 noroviruses. In addition, MucoRice-VHH (7C6-1E4) retained neutralizing activity even after heat treatment at 90°C for 20 min. These results build a fundamental platform for the continued development of MucoRice-VHH heterodimer as a candidate for oral immunotherapy and for prophylaxis against GII.4 and GII.17 noroviruses in not only healthy adults and children but also immunocompromised patients and the elderly.